Рецензия на: Graham Parkes, How To Think About The Climate Crisis. A Philosophical Guide to Saner Ways of Living, London New York: Bloomsbury Academic, 2021. ISBN 978-1-3501-5886-3. 272 p. - Ботева-Рихтер , Бианка (Философский полилог, 2021)
Рецензия